SMART WATER IRRIGATION SYSTEM USING IoT - Ramkumar, P.; Uma, R.; Valarmathi, R. (The journal of contemporary issues in business and government, 2021)
Agriculture is very significant for India. Since, the people of India mostly depend on agriculture for their livelihood. Farming has seen a number of technological transformations in the last decades, becoming more industrialized and technology-driven. By using various smart agriculture gadgets, farmers have gained better control over the process of raising livestock and growing crops, making it more predictable and efficient. Incumbently a technology play an indispensible role for the development of this agricultural country and farming is also solemnly depends on water. Water irrigation is one of the methods to supply water in their farms but in some occasion it might be wasted. The traditional water irrigation system is very difficult due to the scarcity of water which is primarily caused by rapid growth of population and climate. Internet of Things (IoT) is a new methodology to empower the modernization of agriculture. Since through automation Iot can make agriculture and all sorts of farming process in an efficient way by reducing human interventions. So, due to this, it is proposed a novel method called automation of water irrigation system using IoT to save water and time. In this novel approach it is planned to use various sensors such as temperature, humidity, soil moisture sensors to measure the different parameters of the soil based on the value of soil moisture will get automatically make the motor status as on or off stage. With respect to these sensed parameters and the status of the motor will be displayed on mobile. Monitoring and collecting data for soil moisture, temperature, humidity and sunlight intensity across multiple fields will improve efficiency of water usage and crop yield of large and local farms and also when the soil in agricultural land becomes dry by using this method the pump will automatically start the flow of water for irrigation. Sensors are deployed on the farms to monitor the status of crops according to the climate changes in light, humidity, temperature, shape and size. Any deviation is identified by the sensors then the status of the crop will be displayed on the farmer’s smart phone.